Clinical role of Ureaplasma parvum and Ureaplasma urealyticum presence in female lower urogenital tract: Is there a place for routine screening and treatment? - Maruška Marovt; Darja Keše; Jovan Miljković; Mojca Matičič (Zdravniški Vestnik, 2014)
Sexually transmitted infections represent major health problem in females all over the world if remained undiagnosed and untreated. They can have adverse influence on reproduction and health of a mother and a newborn. The development of molecular methods has permitted the detection of an array of microbes whose pathologic roles in urogenital infections need to be further studied. Ureaplasmas (Ureaplasma spp.), being originally found in 1954 from male urogenital tract, are prokaryotic cells without a cell wall, ranging from 0.1 to 1 μm in length. Fourteen known Ureaplasma serovars have been divided in two species based on their phenotypic and genotypic features, Ureaplasma parvum and Ureaplasma urealyticum detected and identified separately using polymerase chain reaction assays. Both are generally considered as genital tract commensals. U. urealyticum is most probably associated with male urethritis which has not been found for U. parvum. Recent studies with supposedly healthy women reported their detection rate between 18-87 % for U. parvum and 6-10 % for U. urealyticum. Even though they have been found to be associated with chorioamnionitis, preterm birth and perinatal complications more commonly then other commensals in this region the rising question regarding their pathogenic role in females remains unsolved and the guidelines regarding the diagnostic screening and treatment are inconsistent.   The aim of our paper is to review the microbiological characteristics, diagnostic methods and epidemiology of newly differentiated U. parvum and U. urealyticum, and to assess evidence speaking pro and contra their clinical role in causing lower urogenital tract infection in women. Since both bacteria are susceptible to antimicrobials it is of utmost importance for clinicians to decide whether or not to search for one or both of them routinely and treat accordingly in order to prevent ascending upper genital tract infection as well as complications in pregnancy and newborns.